CLINICAL SIGNIFICANCE OF EPILEPTIFORM ACTIVITY IN ELECTROENCEPHALOGRAM - L. Yu. Glukhova (Русский журнал детской неврологии)
The article is devoted to some issues of sensitivity and specificity of epileptiform activity in the electroencephalogram (EEG). Epileptiform activity – it is sharp waves and spikes on EEG. Normal EEG does not exclude the diagnosis of epilepsy and viсe versa: presence of epileptiform activity on EEG is not necessarily caused by epilepsy. Several EEGs may be needed to detect epileptiform activity in patients with epilepsy. EEG recording during sleep with the use of different activation methods (hyperventilation, rhythmic photic stimulation, sleep deprivation) can increase the probability of epileptiform activity detection. Clinical presentation should be taken into account while interpreting EEG results with registered epileptiform activity. The issues of epileptiform activity classification and differential interpretation of other electrical activity types are also discussed in the article. Main epileptiform patterns, their neurophysiological basis and correlation with clinical manifestations are described.